2018
DOI: 10.1590/1808-057x201804410
|View full text |Cite
|
Sign up to set email alerts
|

Research in auditing: main themes

Abstract: ABSTRACTe passage of the Sarbanes-Oxley Act (SOX) was a turning point in auditing and in auditors practice for the academic world. Research concerning the characterization of academic production related to auditing is in its third decade. Its analysis is accomplished by means of de nition of keywords, abstracts or title, and information on thematic association within the academic production itself in auditing is undisclosed. In order to revise this gap in auditing literature, this study identi ed the main them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 99 publications
0
1
0
Order By: Relevance
“…Dessarte, a GC cruza as fronteiras disciplinares, incluindo as contribuições para as áreas do conhecimento da administração, contabilidade, direito, economia, estratégia, finanças dentre outras, colocando assim em relevo a interdisciplinaridade e a própria característica colaborativa das pesquisas científicas sobre a GC (Kushkowski et al, 2020;Ribeiro, 2021). E outra área do conhecimento que se conecta diretamente com a GC é a contabilidade (Porte, Saur-Amaral & Pinho, 2018), especialmente levando em consideração a transparência das informações (Ribeiro, 2020).…”
Section: Governança Corporativaunclassified
“…Dessarte, a GC cruza as fronteiras disciplinares, incluindo as contribuições para as áreas do conhecimento da administração, contabilidade, direito, economia, estratégia, finanças dentre outras, colocando assim em relevo a interdisciplinaridade e a própria característica colaborativa das pesquisas científicas sobre a GC (Kushkowski et al, 2020;Ribeiro, 2021). E outra área do conhecimento que se conecta diretamente com a GC é a contabilidade (Porte, Saur-Amaral & Pinho, 2018), especialmente levando em consideração a transparência das informações (Ribeiro, 2020).…”
Section: Governança Corporativaunclassified
“…Of the total, 13.29% had auditing expertise as a subject area, and 3.78% used discourse analysis as a data analysis technique. Porte, Saur-Amaral, and Pinho (2018) reported that 5% of the articles published in the Web of Science had audit procedures as a theme in the period of 2002-2014. Additionally, we performed a search for articles published between 2015 and 2019 in the Science Direct database, using "analytical procedure" or "analytical review" AND "audit" as the search string.…”
Section: Introductionmentioning
confidence: 99%
“…Desde a adoção das referidas normas, diversas pesquisas têm sido desenvolvidas com vistas a verificar suas implicações empíricas (Ge & McVay, 2005;Lopes et al, 2019;Porte et al, 2018). Os estudos anteriores que analisaram a associação entre as DCIs e a QA e/ou informação contábil já documentaram que: (i) existe forte associação entre a divulgação de DCIs e a ocorrência de fraudes subsequentes (Donelson et al, 2017); (ii) o pacote de remuneração dos empregados e gestores reduz a probabilidade de ocorrência de uma DCI e a reapresentação das demonstrações financeiras (Guo et al, 2016;Hoitash et al, 2012); (iii) a estratégia empresarial está associada à ocorrência de uma DCI e à QA (Bentley-Goode et al, 2017); (iv) a associação entre a adoção da norma de divulgação de DCIs e o gerenciamento de resultados ainda é controversa (Amoah et al, 2017;Foster & Shastri, 2012;Lenard et al, 2016;Lu et al, 2011); (v) a divulgação de DCIs está associada a um maior audit delay (Munsif et al, 2012); e (vi) a divulgação de DCIs está associada à reapresentação das demonstrações financeiras subsequentes e o mercado reage negativamente à sua divulgação (Li et al, 2018).…”
Section: Introductionunclassified